The Reality of Islamic Anthropology Through Halal Food: Evidence from Tokyo Prefecture, Japan - Dahlan, Ahmad; Voak , Adam; Aprianto, Naerul Edwin Kiky (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
This study investigates Islamic practices in Tokyo, Japan, examining their role as a unifying force thattranscends ethnic, national, and cultural boundaries. Based on field research conducted in 2024, the studyanalyzes the dynamics of Tokyo’s diverse Muslim community, which encompasses practitioners from variedglobal backgrounds. Through systematic interviews and participant observation, the research reveals how thehalal industry functions as a primary mechanism for promoting inclusive and tolerant Islamic teachings. Thegradual expansion of Islam in Tokyo since the 2000s has been characterized by practices that fostercultural inclusion and social cohesion. The concept of halal food emerges as an exemplar of Islamicpluralistic principles, serving as a bridge between different faith communities and cultural traditions. Thisphenomenon aligns with the Qur’anic principle of unity in diversity (QS 49:13), demonstrating thepractical manifestation of Islamic teachings on pluralism within a contemporary urban context. The findingsindicate that the halal trade serves as both a medium for religious expression and a catalyst for culturalharmony in Tokyo. This research contributes to the cultural anthropology literature by illuminatingpreviously underexplored dynamics of cultural adaptation and religious pluralism within Japan’s urbanlandscape.